2022
DOI: 10.1186/s12866-021-02426-5
|View full text |Cite
|
Sign up to set email alerts
|

High genetic heterogeneity of Mycobacterium intracellulare isolated from respiratory specimens

Abstract: Background M. intracellulare is a frequent causative pathogen of nontuberculous mycobacteria infection that causes infections in the respiratory tract, whose incidence is increasing in many countries. This study aimed at determining the VNTR-based genetic diversity of a collection of 39 M. intracellulare human strains isolated from respiratory specimens over the last 5 years. Results The VNTR analysis showed that M. intracellulare strains displayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Our results show that the genetic characteristics of clinical isolates of M. intracellulare are not related to geographical location, which is consistent with the previous reports with VNTR analyses ( 29 , 30 ). In contrast to M. intracellulare , the genetic characteristics and molecular epidemiology of clinical strains of the MP-MIP group are poorly understood.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results show that the genetic characteristics of clinical isolates of M. intracellulare are not related to geographical location, which is consistent with the previous reports with VNTR analyses ( 29 , 30 ). In contrast to M. intracellulare , the genetic characteristics and molecular epidemiology of clinical strains of the MP-MIP group are poorly understood.…”
Section: Discussionsupporting
confidence: 93%
“…With genetic sequencing increasingly affordable, the MP-MIP group strains can be detected more frequently in the future. Though variable numbers of tandem repeats (VNTR) analysis has been a highly discriminatory tool in molecular epidemiology analysis, it is unable to classify the M. intracellulare and related strains such as MP and MIP ( 29 ). A previous study found that there are 4% of M. intracellulare isolates that have been identified as MIP by sequence-based typing analyses ( 15 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, M. intracellulare has been reported to be responsible for the largest proportion of MAC-PD cases ( Prevots and Marras, 2015 ; Chang et al, 2020 ; Ratnatunga et al, 2020 ). Mycobacterium intracellulare can be found in any environment, including soil, water, and air, and molecular epidemiology has revealed considerable genetic variation in its strains ( Hruska and Kaevska, 2012 ; Parker et al, 2020 ; Lari and Rindi, 2022 ). MAC reinfection and redevelopment of MAC-PD can result from exposure to these environmental sources or regrowth of previously infected strains.…”
Section: Introductionmentioning
confidence: 99%